Pencarian Dasar-dasar Filosofis bagi Keberadaan Filsafat Nusantara - Kartika, Ganang Dwi (UI Scholars Hub, 2004)
The meaning of philosophy in Indonesian has become an interesting topics, especially when it is related to another concept, culture. Some Indonesian dictionary writers defined